Exploring cryptic amyloidogenic regions in prion-like proteins from plants - Pintado-Grima, Carlos; Santos, Jaime; Iglesias, Valentín; Manglano-Artuñedo, Zoe; Pallarès, Irantzu; Ventura, Salvador (Frontiers in Plant Science, 2023)
Prions are a particular type of proteins that can transition via a conformational switch between soluble and aggregated states. Regions of moderate amyloid propensity within disordered prion-like domains play a pivotal role in structural conversion. These amyloidogenic regions are rich in polar amino acids and escape from the detection of classical bioinformatics screenings that look for highly aggregation-prone hydrophobic sequence stretches. In recent work, we demonstrated the prevalence of cryptic amyloidogenic regions (CARs) in intrinsically disordered proteins and developed an integrated database (CARs-DB) that collects thousands of predicted amyloidogenic sequences of polar nature. Here we have focused on identifying and characterizing CARs in prion-like proteins from plants (pCARs), a lineage that has been poorly studied in comparison with other prionomes. We confirmed amyloid formation for a selected pCAR from Arabidopsis thaliana and explored functional enrichments and compositional bias of cryptic amyloid-prone segments in plant prion-like proteins.